Criminal Offenses Committed by Civilians Together With Members Of The Military - Tamba, Handika Syahputra; Esther, July; Sinaga, Jusnizar (Indonesian Journal Publisher, 2025)
The Military Court can only deal with such cases if there is a decision by the Minister of Defense and Security, approved by the Minister of Justice, to transfer it to a military court. This decision is usually based on consideration of the degree of harm caused to military interests. Based on the types and sources of data used in this research, the author applies normative qualitative research methods. Normative qualitative research is an approach carried out through literature studies by utilizing various references, such as laws, books, journals, theses, and laws and regulations relevant to the formulation of research problems Conflicting sentences reflect the complexity of the criminal justice system involving various legal institutions, such as military police, civilian police, military prosecutors. The handling of this case requires good coordination between institutions to ensure a transparent legal process, in accordance with applicable regulations. This mechanism aims to accommodate equal legal treatment of perpetrators, both members of the military and civilians, while maintaining military discipline, the rule of law. Conflicting crimes reflect the complexity of the criminal justice system in Indonesia, because they involve two different legal jurisdictions. The mechanisms set out in the Military Justice Law aim to ensure justice for perpetrators and victims, while still considering the efficiency and effectiveness of the legal process. The handling of koneksitas cases requires cross-institutional cooperation to ensure a fair and transparent legal process.